2018
DOI: 10.1007/s11128-018-2084-6
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement criterion via general symmetric informationally complete measurements

Abstract: We study the quantum separability problem by using general symmetric informationally complete measurements and present a separability criterion for arbitrary dimensional bipartite systems. We show by detailed examples that our criterion is more powerful than the existing ones in entanglement detection.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
(97 reference statements)
0
13
0
Order By: Relevance
“…Interestingly, if we choose MUMs or GSIC-POVMs as local measurements for the two subsystems, respectively, then the separability criteria determined by equations (11), ( 13), ( 15) and ( 16) can recover the ones in [36][37][38][39][40][41][42], as summarized in table 2.  by…”
Section: Letmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, if we choose MUMs or GSIC-POVMs as local measurements for the two subsystems, respectively, then the separability criteria determined by equations (11), ( 13), ( 15) and ( 16) can recover the ones in [36][37][38][39][40][41][42], as summarized in table 2.  by…”
Section: Letmentioning
confidence: 99%
“…Moreover, unlike the MUBs and SIC-POVMs, the complete set of MUMs and GSIC-POVMs can be constructed explicitly in all finite dimensions. These measurements are widely applied to the detection of entanglement, and thus a series of efficient separability criteria have been proposed both for bipartite and multipartite systems to date [36][37][38][39][40][41][42][43][44][45]. It has been shown that the existing criteria based on MUMs and GSIC-POVMs are very powerful in detecting the entanglement of bipartite quantum states, however, how to construct efficient criteria for multipartite quantum states is in general a hard issue.…”
Section: Introductionmentioning
confidence: 99%
“…We discuss in this section testers coming from spherical 2-designs; an important special case corresponds to the entanglement criterion based on SIC POVMs introduced in [SAZG18, Section IV] (see also [LLFW18]). Given a spherical 2-design {|x k } d 2 k=1 of C d with d 2 elements (see equation ( 14) below for the definition), the set…”
Section: Important Examples Of Testersmentioning
confidence: 99%
“…Uncertainty relations of GSIC POVMs are studied in different contexts such as the entropic uncertainty relation [15], the uncertainty and complementarity relation using generalized Wigner-Yanase-Dyson skew information [16], and the improved state-dependent entropic uncertainty relation [17]. Entanglement detection using the index of coincidence for GSIC POVMs as well as its experimental implementation has also been studied in [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%